Systematic paleobotany from the Agua de la Zorra Formation (Upper Triassic), Mendoza, Argentina - Pedernera, Tomas Ezequiel (2018)
The Triassic Cacheuta Group crops out in the North-west of Mendoza Province, and includes from base to top, four units: Paramillos, Agua de la Zorra, Portezuelo Bayo and Los Colorados formaVons. The Agua de la Zorra FormaVon is dominated by bituminous shales and marls, and subordinated intercalaVons of fine-grained sandstones and mudstones. Few levels of peperiVc and olivine basalts are interbedded in the shale facies. The deposiVonal system is interpreted as fluviolacustrine with episodic subaqueous incursions of lava. The age of this unit was referred to the Middle to Late Triassic. The aim of this contribuVon is to analyze the new plant material found in the Agua de la Zorra FormaVon from a systemaVc and taxonomic point of view. The remains of plant megafossils were collected systemaVcally throughout the secVon at Paramillos de Uspallata. Plant remains were referred to 16 species, included in six taxonomic groups and one insertae sedis taxon (IANIGLA-PB 672-739). Equisetaceae (Neocalamites sp.), Osmundaceae (Cladophlebis mesozoica and C. mendozaensis.), Corystospermales (Dicroidium argentum, D. crassum, D. odontopteroides, Johnstonia coriacea, J. sterlzeriana, Xylopteris argen0na, X. elongata, Zuberia feistmanteli and Z. zuberi), Cycadales (Taeniopteris sp.), Ginkgoales (Sphenobaiera sp.), Voltziales (Heidiphyllum elongatum), Podocarpaceae (Rissikia media), and insertae sedis leaves Lingufolium cf. patagonicum, were recognized. The material studied increases in 12 taxa the exisVng record enriching our knowledge of the paleoflora of the Agua de la Zorra FormaVon.